2020
DOI: 10.21203/rs.2.24568/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LINC01006 facilitates cell proliferation, migration and invasion in prostate cancer through targeting miR-34a-5p to up-regulate DAAM1

Abstract: Background: Prostate cancer (PCa) is a kind of malignancy occurring in the prostate gland. Substantial researches have proved the major role of long noncoding RNAs (lncRNAs) in PCa. However, the role of long intergenic non-protein coding RNA 1006 (LINC01006) in PCa has not been investigated yet.Methods: RT-qPCR was used to examine the expression levels of LINC01006 and its downstream targets. The function of LINC01006 in PCa was tested by in vitro and in vivo assays. With application of RNA pull down, RNA immu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…DAAM1 was discovered to have oncogenic function in ovarian cancer via inhibiting the expression of miR‐208a‐5p expression 32 . In addition, DAAM1 could facilitate prostate cancer cell proliferation, migration, and invasion via LINC01006/miR‐34a‐5p axis 33 . In this study, DAAM1 was determined to be the target gene of miR‐188‐5p and its expression was detected to be high in OSCC cells.…”
Section: Discussionmentioning
confidence: 74%
“…DAAM1 was discovered to have oncogenic function in ovarian cancer via inhibiting the expression of miR‐208a‐5p expression 32 . In addition, DAAM1 could facilitate prostate cancer cell proliferation, migration, and invasion via LINC01006/miR‐34a‐5p axis 33 . In this study, DAAM1 was determined to be the target gene of miR‐188‐5p and its expression was detected to be high in OSCC cells.…”
Section: Discussionmentioning
confidence: 74%
“…A RT-qPCR tested miR-34a-5p expression in HCT-116 cells after miR-34a-5p inhibition; B MTT tested viability of HCT-116 cells after miR-34a-5p inhibition; C flow cytometry tested apoptosis of HCT-116 cells after miR-34a-5p inhibition; D Transwell assay tested migration of HCT-116 cells after miR-34a-5p inhibition; E Transwell assay tested invasion of HCT-116 cells after miR-34a-5p inhibition; F RT-qPCR tested Ecadherin mRNA expression in HCT-116 cells after miR-34a-5p inhibition; G RT-qPCR tested N-cadherin mRNA expression in HCT-116 cells after miR-34a-5p inhibition; H RT-qPCR tested Vimentin mRNA expression in HCT-116 cells after miR-34a-5p inhibition; I RT-qPCR tested Snail mRNA expression in HCT-116 cells after miR-34a-5p inhibition; the data were expressed as mean ± standard deviation of three independent experiments. * P < 0.05 compared with the NC-inhibitor group morphogenesis 1, thus to accelerate cancer development [53]. As to liver cancer, miR-34a-5p exerts anti-proliferative, anti-migratory, and anti-invasive effects on cancer cells through targeted regulation of Yin and Yang 1 [54].…”
Section: Discussionmentioning
confidence: 97%
“…LINc01006 is upregulated in prostate (20) and pancreatic (21) cancers and plays pro-oncogenic roles. By contrast, this lncRNA is weakly expressed in gastric cancer and exhibits a notable association with age, tumor location, tumor size and venous invasion (22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed the abnormal expression of the long intergenic non-protein-coding RNA 1006 (LINc01006) in prostate (20), pancreatic (21) and gastric (22) cancers. However, whether LINc01006 plays important roles in cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 88%